Photocatalytic Degradation Of Phenol In Fluidized Bed Reactor Using TiO2-P25/Activated Carbon Prepared By Modified SOL-GEL Method - Lam , Sze Mun (2010)
TiO2-P25 immobilized on activated carbon (TPA) was successfully prepared by modified sol-gel method. The study included optimization of calcination temperature and P25 loading in the photocatalyst preparation. Experiments on the photocatalytic degradation of phenol in a fluidized bed reactor showed that the photocatalytic activity of the prepared photocatalyst can be significantly improved by increasing the calcination temperature from 400 to 600oC, which was due to an increase in both the anatase and rutile crystalline material and increase slightly in BET surface area, total pore volume and average pore size. It was found that the optimum calcination temperature in the photocatalyst preparation was 600oC.